miR-636: A Newly-Identified Actor for the Regulation of Pulmonary Inflammation in Cystic Fibrosis - Bardin, Pauline; Foussignière, Tobias; Rousselet, Nathalie; Rebeyrol, Carine; Porter, Joanna C.; Corvol, Harriet; Tabary, Olivier (Frontiers in Immunology, 2019)
Cystic fibrosis (CF) results from deficient CF transmembrane conductance regulator (CFTR) protein activity leading to defective epithelial ion transport. Pulmonary degradation due to excessive inflammation is the main cause of morbidity and mortality in CF patients. By analysing miRNAs (small RNAseq) in human primary air-liquid interface cell cultures, we measured the overexpression of miR-636 in CF patients compared to non-CF controls. We validated these results in explant biopsies and determined that the mechanism underlying miR-636 overexpression is linked to inflammation. To identify specific targets, we used bioinformatics analysis to predict whether miR-636 targets the 3’-UTR mRNA regions of IL1R1 and RANK (two pro-inflammatory cytokine receptors), IKBKB (a major protein in the NF κB pathway), and FAM13A (a modifier gene of CF lung phenotype implicated in epithelial remodelling). Using bronchial epithelial cells from CF patients to conduct a functional analysis, we showed a direct interaction between miR 636 and IL1R1, RANK, and IKBKB, but not with FAM13A. These interactions led to a decrease in IL1R1 and IKKβ protein expression levels, while we observed an increase in RANK protein expression levels following the overexpression of miR 636. Moreover, NF κB activity and IL 8 and IL-6 secretions decreased following the transfection of miR-636 mimics in CF cells. Similar but opposite effects were found after transfection with an antagomiR-636 in the same cells. Furthermore, we demonstrated that miR-636 was not regulated by Pseudomonas aeruginosa in our model. We went on to show that miR-636 is raised in the blood neutrophils, but not in the plasma, of CF patients and may have potential as a novel biomarker. Collectively, our findings reveal a novel actor for the regulation of inflammation in CF, miR-636, which is able to reduce constitutive NF κB pathway activation when it is overexpressed.